2022
DOI: 10.3389/fped.2022.791815
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Administration Following Hypoxia-Induced Neonatal Brain Damage Attenuates Later-Life Seizure Susceptibility and Anxiety-Related Behavior: Modulating Inflammatory Response

Abstract: BackgroundNeonatal seizures commonly caused by hypoxia could lead to brain injury and cognitive deficits. Quercetin could cross the blood brain barrier and exerts neuroprotective effects in many neurological disease settings. In this study, we aim to investigate the role of quercetin in attenuating cognitive impairment following hypoxia-induced neonatal seizure (HINS).MethodSprague-Dawley rats at P7 were exposed to a premixed gas in a hypoxic chamber to induce brain injury, and then continuously administered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated increased levels of microgliosis and cytokine release, particularly IL‐1β, in this hypoxia‐induced neonatal seizure model, with this being associated with neuronal damage and aberrant neuron morphology in the hippocampus in later life (Quinlan et al, 2019). Moreover, targeting inflammation during hypoxia has shown success in reducing neonatal seizure severity and to alleviate adverse long‐term clinical outcomes (Quinlan et al, 2019; Wu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated increased levels of microgliosis and cytokine release, particularly IL‐1β, in this hypoxia‐induced neonatal seizure model, with this being associated with neuronal damage and aberrant neuron morphology in the hippocampus in later life (Quinlan et al, 2019). Moreover, targeting inflammation during hypoxia has shown success in reducing neonatal seizure severity and to alleviate adverse long‐term clinical outcomes (Quinlan et al, 2019; Wu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, reducing inflammatory signalling has anticonvulsant effects in multiple seizure models (Leavy & Jimenez Mateos, 2020). More specifically, blocking inflammation with the anti‐inflammatory drugs candesartan and quercetin was effective in protecting from neonatal seizures and the resultant brain hyperexcitability in mice and rats, respectively (Quinlan et al, 2019; Wu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lower concentrations of Quercetin were observed to have positive effects on shoaling behavior and anxiety in Zebra sh [17]. Quercetin, known for its mitochondrial protective properties, shows potential in treating anxiety induced by methylamphetamine (MA) [18] and can also mitigate anxiety resulting from hypoxia-induced neonatal seizures (HINS) [19] by down-regulating the in ammatory response through the TLR4/NF kappa B pathway. Atropine, an anticholinergic drug, has the potential to serve as adjunctive therapy for Ketamine sedation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another flavonoid, quercetin, which is enriched in Allium cepa [ 85 , 86 ] and several common fruits and vegetables, has shown potent anti-inflammatory action by inhibiting the TLR4/NF-kB signaling in animal models of epilepsy [ 85 , 86 ]. In the same vein, in KA-injected rats, rutin from Ruta graveolens , attenuated the release of inflammatory molecules like IL-1β, IL-6, TNF-α, and high-mobility group box 1 (HMGB1) protein and suppressed the IL-1R1 and toll-like receptor 4 (TLR4) expression, preventing seizures [ 87 ].…”
Section: Methodsmentioning
confidence: 99%